Improving Health Care Delivery through Islamization of Medical practice - Rathor, Mohammad Yousuf; Shah, Azarisman SM (IIUM Medical Journal Malaysia, 2018)
Advances in modern science and technology have not only reduced mortality from communicable diseases but increased physical comfort, life expectancy and quality of life. However its advances have generated changes in the moral values and basic philosophies of mankind, a bi-product being loss of faith in religion as a partner in healing. This has resulted in changes in lifestyle, moral degradation, laxity in sexual behaviours, and disrupting social values. New diseases caused by negative lifestyles such as sexual promiscuity, alcoholism, illicit drug use and smoking, take the greatest toll in terms of deaths and disability among young people. As a consequence, relevant international organizations have supported more novel approaches to health promotion.Good health is the basic requirement of every human being and one of the greatest blessings of ALLAH (SWT) on mankind. The Islamic way of life is a system of divine principles sent by Allah swt through revelation on Prophet Muhammad (saw) which covers physical, intellectual and spiritual needs of human life. It has many constructive ideas to offer in the field of health care and medical practice. It contains many teachings that urge nurturing of one’s health and rejecting any behaviour, which are contradictory to health. Therefore by adopting an “Islamic way of life” we can promote behavioural change. Since Islam encourages adoption of modern technology and science in support of a greater good, we must understand it and adopt all that is good in it and propagate it in the spirit of Tawhid (Unity of God), for the benefit of all humanity. This paper seeks to analyse how medical professionals can promote healthy behaviour to specific target groups and public in general through teachings of Islam.